2021
DOI: 10.1186/s40795-021-00418-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status and associated factors among people living with HIV/AIDS in Ghana: cross-sectional study of highly active antiretroviral therapy clients

Abstract: Background Nutrition among people living with HIV/AIDS (PLWHA) is essential in their care and management as it has implication for their immune function. We examined the nutritional status and associated factors among HIV positive clients accessing Highly Active Anti-Retroviral Therapy (HAART) at a public hospital in Ghana. Methods This was a descriptive cross-sectional study of 152 clients. Anthropometric measurements for weight and height were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…This is in line with other studies done in different parts of the world, for instance in Tanzania, 19.5%, [7] Senegal, 19.2% [8], Ethiopia Arba Minch area, 18.2% [14] and in Nepal, 19.9%. [22] However, it was higher compared to studies conducted in Zimbabwe, 10% , [11] in Ghana 13.8% [9], in Uganda 10.28% [10] and in Ethiopia in Dilla university hospital 12.3%. [15] On the other hand, higher prevalence of undernutrition was reported in different regions of Ethiopia including in Tigray (42.3%) [12] and in Jimma Medical Center (34.0%) [13] and in Nigeria which reported at 43.3%.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This is in line with other studies done in different parts of the world, for instance in Tanzania, 19.5%, [7] Senegal, 19.2% [8], Ethiopia Arba Minch area, 18.2% [14] and in Nepal, 19.9%. [22] However, it was higher compared to studies conducted in Zimbabwe, 10% , [11] in Ghana 13.8% [9], in Uganda 10.28% [10] and in Ethiopia in Dilla university hospital 12.3%. [15] On the other hand, higher prevalence of undernutrition was reported in different regions of Ethiopia including in Tigray (42.3%) [12] and in Jimma Medical Center (34.0%) [13] and in Nigeria which reported at 43.3%.…”
Section: Discussionmentioning
confidence: 66%
“…However, SSA in particular, has the highest prevalence of undernutrition worldwide among PLWHA. Studies done in different parts of the SSA reported 43.3% in Nigeria, [6] 19.5% in Tanzania , [7] 19.2% in Senegal , [8] 13.8% in Ghana, [9] 10.28% in Uganda [10], 10% in Zimbabwe, [11] and in different parts of Ethiopia it was indicated 42.3% , [12] 34.0% , [13] 18.2% , [14] and 12.3%. [15] The factors that are associated with undernutrition among PLWHA range from personal to underlying level factors.…”
Section: Introductionmentioning
confidence: 99%
“…The overall magnitude of overweight/obesity in this study is also lower than that of previous study conducted in South Africa 39%, 25 and Gahanna 28.3%. 26 The possible explanation for this higher discrepancy might be due to socio-economic status, healthcare delivery system and socio-cultural variations. In this study around 65.5% of the study participants had household food insecurity that could expose them to undernutrition rather than overweight /obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 44 included studies, only one was a retrospective cohort and the rest were carried out using cross-sectional study designs. The largest number of articles (33 studies) were reported from Ethiopia [8, and only one article is reported from Kenya [71], Botswana [72], Ghana [73], Democratic Republic of Congo (DRC) [74], Senegal [75], Uganda [76], and Zimbabwe [77]. Four articles were from each of South Africa [78,79] and Tanzania [13,80].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%